Language and power relations: Consequences for a language policy - Harvey, Penelope (1987)
Mannheim observed the following regarding the "Andean linguistics debate": "On the one hand, 'dualistic' models of society assume that language policy involves intervention in what would otherwise be a sui-genus exchange of allegiances by individuals of one cultural group to another, and that the mere existence of a large and geographically concentrated population of indigenous-speaking people indicates superficial and recent contact between the groups; on the other hand, models of internal colonization assume that the maintenance of the indigenous language for a long time indicates that it is a convenience that provides the opportunity for economic exploitation and political control...